Does Regulations of in Peer to Peer Lending has Legitimated Hidden Cyber Extortion? a Legal Review - Susamto, Burhanuddin (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 4 (2024): The 7th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2024)
The purpose of this article is to present the results of an analysis of whether P2P lending practices contain elements of covert cyber extortion when viewed from an integrative legal perspective between regulations and Islamic law.  Covert cyber extortion that hides behind contracts is more dangerous than extortion in general because many victims do not feel exploited. The findings of this study conclude that the practice of P2P lending which charges multiple interest rates and fines due to late installment payments which is calculated per day contains elements of hidden cyber extortion legitimated by regulations. Therefore, the concept and regulating for P2P landing in Indonesia should be reviewed immediately so that there are no victims of exploitation. If in research, Islamic banks are considered loan sharks, then the practice of P2P lending, which is based on daily interest and fines, is more than just a loan shark.